Estimating population parameters of broadnose sevengill sharks (Notorynchus cepedianus) using photo identification capture‐recapture. Issue 4 (10th August 2020) - Lewis, Robert; Dawson, Steve; Rayment, William
Abstract: The broadnose sevengill shark ( Notorynchus cepedianus ) is a common high trophic‐level predator around coastal New Zealand. Data on the ecology of the species in New Zealand are severely lacking, and anthropogenic impacts are unquantified. To partially address this, the authors undertook a study of the demographics of a population at Stewart Island. Sampling trips were carried out seasonally from winter 2016 to spring 2017. A baited underwater video system (BUV) was deployed on 133 occasions (mean = 22.2 deployments per season) in a shallow coastal embayment to capture underwater video of N. cepedianus for photo identification of individuals. N. cepedianus was detected on all but one deployment. Images extracted from video recorded the presence of 149 different individuals. Capture‐recapture analysis of these data using robust design methods indicated a seasonal trend in abundance of the population using the study area, ranging from 34 (95% C.I. = 21–55) during winter 2016, to 94 (95% C.I. = 44–199) during spring 2017. This study presents the first data on demographic parameters of N. cepedianus in New Zealand.